Intussusception as a complication of gastrointestinal basidiobolomycosis: A case report - Sara AlNuwaiser; Sarah Allaf; Faisal Mosaad; Abdurrahman Mirza; Rayan A. Ahyad; Ahmed Alawi (Elsevier, 2023)
Introduction: We report an atypical case of gastrointestinal basidiobolomycosis (GIB) presenting with recurrent intussusception. Case presentation: A 5-year-old male presented with abdominal pain and subjective fever for one day and was admitted to our hospital as a case of recurrent intussusception. He was diagnosed with intussusception based on ultrasound and underwent two successful hydrostatic reductions. One day later, he developed abdominal pain and vomiting, a CT scan was done and showed recurrent intussusception. He then developed red-currant jelly stool with right upper quadrant tenderness, and exploratory laparoscopy revealed ilio-colic intussusception to the hepatic flexure, an inflamed appendix, and healthy cecum. Five days after laparoscopic reduction and appendectomy, the abdominal pain and vomiting recurred, he had laboratory findings of marked eosinophilia, and his histopathology report showed basidiobolomycosis. Abdominal ultrasound showed recurrent intussusception. The patient was kept NPO on TPN and intravenous voriconazole and gradually improved to tolerating orally and passing stool regularly. He was discharged on postoperative day 16 on oral voriconazole and CT scan done on 7th month of follow up showed complete resolution of the mass. Conclusion: GIB should be included in the differential diagnosis of recurrent intussusception given the appropriate clinical setting. According to our case, prolonged medical management of the fungal mass can be successful without surgical resection.